Peningkatan Literasi Keuangan Guru: Strategi Cerdas Mengelola Gaji dan Investasi Masa Depan di Yayasan Citra Mandiri Kabupaten Deli Serdang - Petrus Loo; Rebecca Evadine; William Parlindungan Sihombing; Monetarist Butar Butar; Togar Timoteus Gultom (Universitas Methodist Indonesia, 2026)
Teachers play a pivotal role in educating the nation, yet their financial well-being is often overlooked due to low financial literacy. Limited salaries are frequently consumed by immediate spending needs without planning for the future, leaving teachers vulnerable to fraudulent investment schemes or illegal online loans. This community service initiative aims to enhance teachers' financial literacy by introducing smart salary management strategies and future-oriented investment options. The program partnered with teachers from the Citra Mandiri Foundation School in Deli Serdang. The methodology employed included a preliminary survey, a workshop session, a personal budgeting simulation, and a final evaluation. Results indicated an improvement in participants' financial understanding following the training. Teachers are now able to create monthly budget allocations using sound financial formulas and understand legal investment instruments regulated by the Financial Services Authority (OJK). The initiative concludes that periodic financial education is crucial for fostering financial stability and professional peace of mind among educators.